MOTIVATION OF THE ELDERLY AND ELDERLY VISITS TO THE ELDERLY INTEGRATED SERVICE POST (POSYANDU LANSIA) IN KLAMPISAN HAMLET, KEDUNGGEDE VILLAGE, DLANGGU SUB-DISTRICT, MOJOKERTO DISTRICT - Yufi Aris Lestari; Yulianto Yulianto; Aris Hartono; Indrawati Indrawati; Ratna Yunita (Nurse and Health, 2018)
Background. Having a healthy and prosperous life in old age is the hope of every elderly person. In achieving a healthy and prosperous old age, various efforts have been made by the government, one of which is an Elderly Integrated Service Post (Posyandu Lansia) program.